Weight-Reducing Gastroplasty with Roux-en-Y Gastric Bypass: Impact on Vitamin D Status and Bone Remodeling Markers - Biagioni, Maria Fernanda G. [UNESP]; Mendes, Adriana Lúcia [UNESP]; Nogueira, Célia Regina [UNESP]; Paiva, Sergio Alberto Rupp de [UNESP]; Leite, Celso Vieira de Souza [UNESP]; Mazeto, Glaucia Maria Ferreira da Silva [UNESP] (Mary Ann Liebert, Inc., 2014)
Background: Despite the weight loss benefits of bariatric surgery, studies have shown considerably compromised nutritional conditions, particularly in relation to bone metabolism, in patients who have undergone this procedure. The goal of this study was evaluate bone metabolism alterations after gastroplasty through the concentrations of carboxy-terminal cross-linking telopeptides of type-I collagen (CTX) and bone-specific alkaline phosphatase (BSAP) and vitamin D status. Methods: This study, conducted at the Botucatu School of Medicine University Hospital, UNESP, analyzed 22 women with body mass index (BMI) values higher than 35kg/m(2) who had undergone Roux-en-Y gastric bypass (RYGB) surgery, prior to and 3 and 6 months after the procedure. Results: The patients were evaluated in relation to their anthropometric profile. Obese patients showed a vitamin D status that was compatible with moderate depletion, thus correlating negatively with parathyroid hormone (PTH) and positively with CTX. After surgery, 25-hydroxyvitamin D [25(OH)D] and CTX concentrations increased significantly. Other tests (calcium, phosphorus, magnesium, total AP and BSAP, and PTH) did not differ between the times of analysis and remained stable within the range of normality. Body fat correlated only with 25(OH)D concentrations and was inversely proportional to their increase. There was a positive correlation between PTH and CTX prior to surgery. Conclusions: Hypovitaminosis D is prevalent in obese individuals, and RYGB is related to CTX increase without BSAP alteration in the first follow-up semester.